2004
DOI: 10.1016/j.jtcvs.2003.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Early results of endoscopic lung volume reduction for emphysema

Abstract: Endobronchial valve placement is a safe procedure, with significant short-term improvements in functional status, quality of life, and relief of dyspnea in selected patients with emphysema. A larger study with long-term follow-up is therefore warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
75
0
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(83 citation statements)
references
References 17 publications
4
75
0
4
Order By: Relevance
“…In recent years, new surgical and bronchoscopic lung volume reduction techniques have been proposed in an attempt to reduce the typical shortcomings of resectional LVRS [12][13][14][15]. We have developed a nonresectional LVRS technique in awake patients that respects the basic concepts of resectional LVRS but adds some theoretic advantages and can be performed solely with thoracic epidural anesthesia.…”
mentioning
confidence: 99%
“…In recent years, new surgical and bronchoscopic lung volume reduction techniques have been proposed in an attempt to reduce the typical shortcomings of resectional LVRS [12][13][14][15]. We have developed a nonresectional LVRS technique in awake patients that respects the basic concepts of resectional LVRS but adds some theoretic advantages and can be performed solely with thoracic epidural anesthesia.…”
mentioning
confidence: 99%
“…Early studies were based on observational studies and indicated that EBV implantation was safe, but most studies have found that EBV implantation has little benefit (11)(12)(13)(14)(15)(16)(17). A series of early studies indicated that EBV implantation substantially benefited patients in whom the target lobe collapsed and in whom target lung volume reduction (TLVR) was achieved, but TLVR was achieved in only 24.9% of patients (11)(12)(13)(14)(15). Post-procedure quality of life and exercise capacity improved to some extent for patients with no significant collapse of the target lobe, the difference was not statistically significant (16,17).…”
Section: Endobronchial Valves and Intrabronchial Valvesmentioning
confidence: 99%
“…In some studies, ventilation/perfusion scintigraphy of the lungs is routinely performed (11)(12)(13)(14)(15)(16)(17)(18). The state of lung perfusion is usually consistent with the extent of damage (47), but in a few instances the state of lung perfusion and extent of emphysema may differ because local vascular inflammation has induced vascular remodeling, which can also lead to irregularities in pulmonary perfusion (48,49).…”
Section: Other Predictorsmentioning
confidence: 99%
“…[4][5][6] Daha sonra kollateral dolaşımın olmadığı gösterilen lobun segmentleri kapakçıklar kullanılarak oklüde edilir. Kapakçık inspiryumda hava akışına izin vermez, ancak ekspiryumda açılarak hava akışını sağlar ve böylece lob fonksiyon dışı bırakılmış olur.…”
Section: Olguunclassified
“…Yapılan ilk çalışmalarda pnömotoraks en sık göz-lenen komplikasyon olarak bildirilmiştir. [4,10] Bizim üç olgumuzda komplikasyon gözlenmez iken bir olguda işlem sonrası erken dönemde antibiyotik tedavisine yanıt veren postobstrüktif pnomoni gelişti. Postobstrüktif pmönoni işlemin bilinen ve istenmeyen komplikasyonlarından biridir ve kapakçığın kolayca çıkartılabiliyor olması komplikasyonun kötü sonuçlarını kısıtlamaktadır.…”
Section: Tablo 3 Hastaların Takiplerinde Arter Kan Gazı Değişimiunclassified